cos(x) - tan(x)*cos(x) = 0

**Making use of the fact that tan(x) = sin(x)/cos(x), we have:**

cos(x) - [sin(x)/cos(x)]/cos(x) = 0

cos(x) - sin(x) = 0

**Moving sin(x) to the other side, we can see that:**

cos(x) = sin(x)

** Now ask yourself, where on the unit circle is cos(x) =...**

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

cos(x) - tan(x)*cos(x) = 0

**Making use of the fact that tan(x) = sin(x)/cos(x), we have:**

cos(x) - [sin(x)/cos(x)]/cos(x) = 0

cos(x) - sin(x) = 0

**Moving sin(x) to the other side, we can see that:**

cos(x) = sin(x)

**Now ask yourself, where on the unit circle is cos(x) = sin(x)?**

**This occurs only at pi/4 and 5pi/4.**

*Note that at pi/2 and 3pi/2, the tan is undefined.*

**Therefore, the solution set is: {pi/4, 5pi/4}.**

We have to solve cos x-(tan x*cos x)=0 for 0<=x=<2*pi

cos x-(tan x*cos x)=0

=> cos x(1 - tan x) = 0

cos x = 0

=> x = pi/2 and x = 3*pi/2

1 - tan x = 0

=> tan x = 1

=> x = pi/4

**The solution of the equation is x = pi/2, 3*pi/2 and pi/4**